Parental vaccine hesitancy and acceptance of seasonal influenza vaccine in the pediatric emergency department - Strelitz, Bonnie (Vaccine, 2015)
BACKGROUND: Providing influenza vaccine to patients in the pediatric emergency department (PED) is one strategy to increase childhood influenza vaccine uptake. The Parent Attitudes about Childhood Vaccines (PACV) survey is a new tool to identify vaccine-hesitant parents that may facilitate influenza vaccine uptake in the PED. OBJECTIVE: To assess the feasibility of administering the PACV modified for influenza vaccination in the PED setting and to determine whether parental PACV scores are associated with patient receipt of influenza vaccine in the PED. METHODS: We conducted a cross-sectional study in the PED of a tertiary pediatric hospital in Seattle, WA during the 2013–2014 influenza season. English-speaking parents of children aged 6 months to 7 years who were afebrile, medically stable to be discharged home from the PED, and had not already received an influenza vaccine this season were administered a modified version of the PACV. PACV scores (0–100, higher score = higher hesitancy) were dichotomized (<50 and ≥50) consistent with previous validation studies. Feasibility was assessed by determining time to complete the PACV. Our primary outcome was influenza vaccine refusal in the PED. We used multivariable logistic regression to estimate unadjusted and adjusted odds ratios for association between vaccine refusal and dichotomized PACV scores. RESULTS: 152 parent participants were included in the analysis. The median time for administering the PACV was 7 min. The median PACV score was 28, with 74% scoring <50. Parents who scored ≥50 on the PACV had increased odds of refusing the influenza vaccine compared to parents who scored <50 (adjusted OR [95% CI]: 6.58 [2.03–21.38]). CONCLUSION: Administration of the PACV in the PED is feasible, and higher PACV scores in this setting are associated with increased influenza vaccine refusal.